2015
DOI: 10.1007/s10508-015-0587-0
|View full text |Cite
|
Sign up to set email alerts
|

Does Sexual Satisfaction Change With Relationship Duration?

Abstract: Despite a large body of empirical literature on sexual satisfaction, its development over the course of a relationship is still unclear. Only a small number of studies, most of which have relied on cross-sectional data of convenience samples, have explicitly focused on relationship duration, and empirical evidence is mixed. We analyzed how sexual satisfaction changes over the course of a relationship using three waves of the German Family Panel study (pairfam). We concentrated our analyses on young and middle-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(67 citation statements)
references
References 30 publications
2
59
2
4
Order By: Relevance
“…Past research suggests several possible confounds of the relationships being tested. Relationship length has been found to negatively correlate with sexual satisfaction (Schmiedeberg & Schröder, ), and research suggests that religiosity may impact the nature of the association between pornography use and relational outcomes (Perry & Whitehead, ). In addition, age was found to correlate with a number of the model predictors in the preliminary analysis (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Past research suggests several possible confounds of the relationships being tested. Relationship length has been found to negatively correlate with sexual satisfaction (Schmiedeberg & Schröder, ), and research suggests that religiosity may impact the nature of the association between pornography use and relational outcomes (Perry & Whitehead, ). In addition, age was found to correlate with a number of the model predictors in the preliminary analysis (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Examining the effects of these variables in the relationships between aging and SQoL would be an interesting avenue for future research. We also did not account for relationship duration, which is related to SQoL (Schmiedeberg & Schröder, 2016), because it would have been perfectly confounded with the effect of age for people who remained with the same partner between waves of data collection. Finally, the present study has focused on SQoL and aging in the US.…”
Section: Discussionmentioning
confidence: 99%
“…A methodological limitation to this study is that participants were not asked the duration of their relationship, so use of intimate apparel across time could not be measured. Schmiedeberg and Shroder [61] found that sexual satisfaction peaks in the second half of the first year of a relationship and then declines over time. As the relationship progresses, the couple becomes more acquainted with one another and experience mutual life stressors; the couple transitions into the companionate phase, characterized by a state of comfort and commonality [62].…”
Section: Limitations and Future Researchmentioning
confidence: 99%